2022
DOI: 10.1002/lary.30122
|View full text |Cite
|
Sign up to set email alerts
|

Depression Symptoms and Olfactory‐related Quality of Life

Abstract: Objectives: Patients with olfactory dysfunction (OD) frequently report symptoms of depression. The objective of this study was to determine how clinical characteristics and olfactory-related quality of life (QoL) measures associate with the likelihood for major depressive disorders (MDDs).Methods: A total of 192 OD patients were included. Olfactory function was measured using all three subtests of the Sniffn' Sticks test. Olfactory-related quality of life (QoL) was evaluated using the Questionnaires of Olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…Dysosmic patients demonstrated lower scores at the brief QOD-NS, confirming its usefulness in discriminating patients at a higher risk of QoL detriments related to OD. 10 A significant linear correlation between sVAS and SS (both TDI and SS subtests scores) was also observed in our analysis, replicating previous results. 4 A limit of the study is the lack of a control group of patients with no history of OD with or without previous COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Dysosmic patients demonstrated lower scores at the brief QOD-NS, confirming its usefulness in discriminating patients at a higher risk of QoL detriments related to OD. 10 A significant linear correlation between sVAS and SS (both TDI and SS subtests scores) was also observed in our analysis, replicating previous results. 4 A limit of the study is the lack of a control group of patients with no history of OD with or without previous COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown associations between olfactory-related quality of life and affective as well as cognitive dysfunctions. For example, COVID-19 related olfactory dysfunction has been related to mood disturbances ( Llana et al, 2023 ), a higher likelihood of depression ( Liu et al, 2022 ), as well as cognitive dysfunction ( Delgado-Alonso et al, 2022 ). The observed relationship between olfactory dysfunction and quality of life could therefore be mediated by other affective or cognitive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Smell and taste dysfunction has been consistency linked with decreases in quality of life ( 40 , 41 ), as has the presence of long-COVID ( 42 ). Furthermore, recent studies have found significant decreases in health-related quality of life in people with long-COVID syndrome ( 43 ), with one meta-analysis reporting that 58% of people with long-COVID suffering from poor quality of life ( 42 ).…”
Section: Discussionmentioning
confidence: 99%